Innovation addressing climate change challenges : market-based perspectives - Hymel, Mona L.; Kreiser, Larry; Milne, Janet E.; Ashiabor, Hope; Edward Elgar Publishing (Edward Elgar Pub., Inc., 2018)
Although the world faces many environmental challenges, climate change continues to demand attention in both academic and public spheres. Innovation Addressing Climate Change Challenges explores ways in which market-based instruments and complementary policies can help countries meet their climate change goals following the Paris Agreement. In this insightful book, internationally distinguished climate change scholars have come together to examine the potential of a range of market-based instruments. These include carbon pricing, coal subsidies, vehicle taxation, government incentives for the electricity sector, and noise pollution taxes. Offering useful market-based perspectives, the book not only demonstrates the possibilities that these various instruments offer in reducing the risks of climate change, but also the challenges that exist in utilizing them. These insights will help to inform the many climate policy decisions that lie ahead. Astute and forward thinking, this timely book will be of vital importance to both students and scholars of environmental law and environmental economics with a particular focus on climate change. Political science students, as well as government officials, will also find its guidance on future policy engaging and timely.
Contents: Foreword by Janet E. Milne -- Preface -- Part I: Carbon pricing design and prospects -- 1. Introducing carbon taxes - issues and barriers / Stefan Weishaar -- 2. Border adjustment with taxes or allowances to level the price of carbon / Mikael Skou Andersen -- 3. Towards bottom-up carbon pricing in Canada / Takeshi Kawakatsu and Sven Rudolph -- 4. Beyond Thunderdome? The prospects of federal greenhouse gas cap-and-trade in Australia / Elena Aydos and Sven Rudolph -- 5. How market-based emissions reduction mechanisms affect private property in Australia / Vanessa Johnston -- Part II: Complementary tax approaches -- 6. Vehicle taxation in EU member states / Claudia Kettner and Daniela Kletzan-Slamanig -- 7. Cutting Europe's lifelines to coal subsidies / Shelagh Whitley, Laurie van der Burgh, Leah Worrall and Sejal Patel -- 8. Noise pollution taxes: a possibility to explore / Marta Villar Ezcurra -- 9. Tackling environmental pollution in Seoul, South Korea through tax incentives and related strategies / Paul J. Lee, Heidi Hylton Meier and Stephanie Lee -- Part III Revenue perspectives -- 10. Green ICMS - Brazil's tax revenue distribution based on environmental criteria / Lise Tupiassu, Bernardo Mendonca Nobrega and Jean-Raphael Gros-Desormaux -- 11. Climate change-related action and non-productive investments in the European Union / Maria Amparo Grau Ruiz -- 12. Total economic value of the Cagayan de Oro river basin / Rosalina Palanca-Tan, Catherine Roween Chico-Almaden, Ma. Kresna Navarro, Marichu Melendez-Obedencio and Caroline Laarni Rubio-Serenas -- Part IV Incentives for the electricity sector -- 13. Low-income households in New York's reforming the energy visions / Ross Astoria -- 14. Mitigating the environmental consequences of electricity sector "lock in" options for a de-carbonised energy future / Rowena Cantley-Smith -- 15. An overview of zero emission credits for nuclear power plants in the United States / Hans Sprohge and Larry Kreiser -- Index.
Includes index.
Includes bibliographical references.
Keywords: Climate change mitigation -- Government policy; Climatic changes -- Law and legislation; Climatic changes -- Risk management; Electronic books